Bangladesh Ship Breaking Industry: Is it an Opportunity or Obstacles for Out-Migrant Workers? - Chowdhury, Ahmed Imtiaz; Saiful Islam, (Technium Social Sciences Journal, 2024)
The ship breaking industry flourished in Bangladesh after the liberation war in 1971. Since then Bangladesh is leading in this ship breaking sector around the globe. The rapid growth of this industry is specially driven by national iron demands, income generation, and the easy opportunity of employment for the poor people. As most of the workers working here are poor and hail from underdeveloped regions of the country hence this study was designed to find out the obstacles and opportunities that need to encounter when they leave this industry after extensive working years. The instrument used for this research was semi close ended questionnaires, in depth interviews, ethnographic analysis and secondary research. The respondents are from southern and northern parts of Bangladesh, aged 18 years and above. This study revealed that a majority portion of the out migrant workers are sufferings from numerous challenges such as health issue, social stigma, psychological trauma, restricted employment opportunities, limited geographical mobility and so on. Conversely, only a minority of the out migrators are benefited from this industry, specifically those employed in technical or supervisory roles. Overall, this industry has proven detrimental, creating more obstacles rather than opportunities for out-migrant workers lives.